Advancements in Public First Responder Programs for Out-of-Hospital Cardiac Arrest: An Updated Literature Review - Michael Kern; Gerrit Jansen; Bernd Strickmann; Thoralf Kerner (Reviews in Cardiovascular Medicine)
Out-of-hospital cardiac arrest (OHCA) is a leading cause of death worldwide, with a low survival rate of around 7% globally. Key factors for improving survival include witnessed arrest, bystander cardiopulmonary resuscitation (CPR), and early defibrillation. Despite guidelines advocating for the “chain of survival”, bystander CPR and defibrillation rates remain suboptimal. Innovative approaches, such as dispatcher-assisted CPR (DA-CPR) and smartphone-based alerts, have emerged to address these challenges. DA-CPR effectively transforms emergency callers into lay rescuers, and smartphone apps are increasingly being used to alert volunteer first responders to OHCA incidents, enhancing response times and increasing survival rates. Smartphone-based systems offer advantages over traditional text messaging by providing real-time guidance and automated external defibrillator (AED) locations. Studies show improved outcomes with app-based alerts, including higher rates of early CPR, increased survival rates and improved neurological outcomes. Additionally, the potential of unmanned aerial vehicles (drones) to deliver AEDs rapidly to OHCA sites has been demonstrated, particularly in rural areas with extended emergency medical services response times. Despite technological advancements, challenges such as ensuring responder training, effective dispatching, and maintaining responder well-being, particularly during the coronavirus disease 19 (COVID-19) pandemic, remain. During the pandemic, some community first responder programs were suspended or modified due to shortages of personal protective equipment (PPE) and increased risks of infection. However, systems that adapted by using PPE and revising protocols generally maintained responder participation and effectiveness. Moving forward, integrating new technology within robust responder systems and support mechanisms will be essential to improving OHCA outcomes and sustaining effective response networks.